Effect of Adding (Binder-Plastisizer-Lubricat) on the Physical Properties of Kaolin - Baghdad Science Journal (مجلة بغداد للعلوم)
The study concern with the preparation of three type of mixtures; which are prepared from different percentage of polyvenil Butyral, Di-n-butyl phathalate and paraffin wax pastillated. The solvent used is Xylolzul analyses. After washing, Drying and milling the kaolin Dukhla, as a matrix in this study, and by using sieving Tech. The range of particle size used is less than and less than as a mesh batch. The added percentage from prepared mixture were 5% and 10% to 95% and 90% of the matrix respectively. Then disk samples were prepared by using a compaction pressure with heating. After cooling and drying the samples were undergo heat treatment in the range of (1250 – 1350) oC. The measurement of shrinkage and Dielectric properties shows that the satisfied data to be compatible with the industrial properties were for 5% (75%B + 15%P + 10%L) added to 5% to 95% of Kaolin (Particle size less than ); which was fired at 1300oC.